(untitled) (Research, Society and Development, 2022)
Objective: to identify in the available literature how fake news disseminated during the COVID-19 pandemic can lead to the development of negative feelings, such as fear, uncertainty and worry. Methods: this is an integrative literature review, in which the acromion PECO was used to prepare the guiding question of the study. PubMed, BVS and Scielo were used to collect the data, together with the Health Sciences Descriptors (DeCS), combined using the Boolean operator AND. For the selection of articles, inclusion criteria were used, such as: full articles, available in Portuguese, English and Spanish and that addressed the guiding question of the study. Results: searches were carried out in PubMed, Virtual Health Library (BVS) and Scielo databases, resulting in a total of 1251 studies, 490 in PubMed, 550 in VHL and 211 in Scielo. After reading the titles and abstracts, a total of 1149 studies were excluded, 418 in PubMed, 530 in VHL and 201 in Scielo, leaving 102 studies. After a thorough reading of the articles in full, 13 were selected. Final Considerations: it is noteworthy that since the emergence of the new coronavirus, there has been an increase in the spread of fake news related to this new virus, which has contributed to infodemics and feelings of concern by the population.